2017
DOI: 10.1002/jsfa.8445
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterisation and dominance of different hydrolases in different types of Daqu – a Chinese industrial fermentation starter

Abstract: BACKGROUND: Daqu is a fermentative saccharification agent that is used to initiate fermentation in the production of Chinese liquor and vinegar. This study investigated the differences of amylase, protease and esterase in dominance of different types of Daqu, which can be useful for quality control and flavor improvement of Daqu production by enzyme technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 36 publications
2
61
0
Order By: Relevance
“…With increase in production and technological innovation, the production of Daqu has evolved from a simple artisanal process into a large scale industrial process . However, a lack of understanding of the characteristics of Daqu – which is limited to its physicochemical properties and sensory evaluation – causes variability between batches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With increase in production and technological innovation, the production of Daqu has evolved from a simple artisanal process into a large scale industrial process . However, a lack of understanding of the characteristics of Daqu – which is limited to its physicochemical properties and sensory evaluation – causes variability between batches.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, improved understanding of Daqu production by natural fermentation would enable better control of the process and assure the quality of the final product. To achieve this goal, the functional microorganisms that play important roles in Daqu formation must be controlled . Only once this has been achieved can the production of Daqu be transformed from an uncontrolled natural fermentation into a controlled industrial fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Azad Shah, Tokunaga, Kurihara, and Takahashi () reported that lipolysis and lipid oxidation are responsible for the thickness, mouthfulness, and continuity taste in migaki‐nishin, a dried fish product. To date, published studies have focused on proteins (Chou & Ling, ; Kaewkrod, Niamsiri, Likitwattanasade, & Lertsiri, ; Yong & Wood, ) and starch (Elfalleh, Sun, He, Kong, & Ma, ; Liu, Chen, Fan, Huang, & Han, ) degradation and umami peptides (Kim et al., ; Zhuang et al., ) of soy sauce. And the changes of lipid and its relationship with volatile compounds have been investigated during the koji fermentation of soy sauce (Feng et al., , ; Gao et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Amylase is a major contributor to the liquefaction and saccharification processes of Daqu (Li et al ., ; Liu et al ., ). Therefore, amylase activity was used as a criterion to optimise the optimal ratio of inoculation.…”
Section: Resultsmentioning
confidence: 97%